Applicaton of Digital Shoreline Analysis System (DSAS) for analyzing sandy coast dynamics in Essaouira, Morocco - Khouz, Abdellah (2024)
Coastlines change research plays a crucial role in understanding the evolution and ensuring effective risk management. This is essential for minimizing impacts on the environment and society. Our study aims to assess the coastal dynamics of sandy systems in Essaouira. By employing advanced techniques such as DSAS and GIS, we aim to analyze shoreline changes, erosion rates, and susceptibility to sand movement. The insights gained from our investigation into the sandy coastal system will provide valuable input for making informed decisions regarding territorial management.